Appropriate PD-L1 Cutoff Value for Gastric Cancer Immunotherapy: A Systematic Review and Meta-Analysis - Xie, Tong; Zhang, Zhening; Zhang, Xiaotian; Qi, Changsong; Shen, Lin; Peng, Zhi (Frontiers in Oncology, 2021)
Background Immunotherapy dramatically changed the treatment landscape of gastric cancer in recent years. PD-L1 expression was proposed as a biomarker; however, the treatment strategy according to PD-L1 is still uncertain. Here, we aimed to find the appropriate cutoff value of PD-L1 expression for gastric cancer immunotherapy. Methods We did a systematic electronic research of prospective clinical trials of gastric cancer immunotherapy across databases. Studies that provided subgroup analysis results stratified by PD-L1 expression were included. Objective response rate (ORR), disease control rate (DCR), hazard ratio (HR), and 95% confidential interval (CI) of progression-free survival (PFS) and overall survival (OS) at different PD-L1 cutoff values were extracted. Results Twelve studies and 6,488 patients in total were finally included for pooled analysis. ORR in allover, PD-L1-negative, combined positive score (CPS) ≥1, CPS ≥5, and CPS ≥10 population was 10%, 3%, 13%, 20%, and 23%, respectively. Immune checkpoint inhibitor (ICI) monotherapy failed to show survival advantage in allover and PD-L1-negative patients. Single-agent ICI therapy prolonged OS (HR = 0.84, 95% CI: 0.74–0.96) but not PFS (HR = 1.38, 95% CI: 0.91–2.09) in PD-L1 CPS ≥1 patients. For combined immunotherapy, ORR in allover, PD-L1-negative, CPS ≥1, CPS ≥5, and CPS ≥10 population was 64%, 57%, 48%, 60%, and 58%, respectively. Allover population could gain survival benefit from combined immunotherapy based on the results from Checkmate-649. OS (HR = 0.81, 95% CI: 0.71–0.92) and PFS (HR = 0.77, 95% CI: 0.69–0.86) were significantly prolonged in PD-L1 CPS ≥1 patients receiving combined immunotherapy. Conclusion Efficacy and survival advantages improved with PD-L1 CPS. CPS ≥1 was the cutoff value for ICI monotherapy to gain survival benefit. Combined immunotherapy prolonged PFS and OS in allover population but needs further study to confirm it.